2018
DOI: 10.1186/s12879-018-3372-6
|View full text |Cite
|
Sign up to set email alerts
|

Virological failure among adolescents on ART, Harare City, 2017- a case-control study

Abstract: BackgroundZimbabwe is on track towards achieving viral suppression among adults (87%). However, adolescents have only achieved 44% by 2016. In Harare city, 57% of adolescents had attained viral suppression after 12 months on ART compared to 88% among adults. We determined factors associated with virological failure among adolescents (age 10–19 years) on antiretroviral therapy (ART) in Harare city.MethodsWe conducted a one to one unmatched case control study among 102 randomly recruited case: control pairs at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
81
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(95 citation statements)
references
References 16 publications
14
81
0
Order By: Relevance
“…It has been previously reported that ALHIV not disclosed of their HIV-serostatus increases virological failure by a 5-fold [53]. The identi cation of virological failure is possible where viral load measurement is available, which was not routinely done in West Africa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been previously reported that ALHIV not disclosed of their HIV-serostatus increases virological failure by a 5-fold [53]. The identi cation of virological failure is possible where viral load measurement is available, which was not routinely done in West Africa.…”
Section: Discussionmentioning
confidence: 99%
“…The COHADO study is one of the rst cohort to provide viral load data in West-Africa, with measurements substantially more available after 24 months of followup. Viral load access is a real issue in ALHIV care monitoring in Africa, and the prioritization of viral load measurement is universally recommended since 2016 particularly for ALHIV who have high risk of virological failure [53]. In the COHADO clinical sites, the annual viral load measurement is a recent opportunity that should be scaled up and supported in every HIV-care facility, as virological success could be also an indicator used to encourage treatment adherence and therefore outcomes of APHIV.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously reported that ALHIV non-disclosure of HIV-serostatus increases virological failure by a 5-fold [53]. The identification of virological failure is possible where viral load measurement is available, which was not routinely done in West Africa.…”
Section: Discussionmentioning
confidence: 99%
“…The COHADO cohort is one of the first study to provide viral load data in West-Africa, with measurements more available at the 24 th month of follow-up. Viral load access is a real issue in ALHIV care monitoring in Africa, and the prioritization of viral load measurement is universally recommended since 2016 particularly among ALHIV who have high risk of virological failure [53]. In the COHADO clinical sites, the annual viral load measurement is a recent opportunity that should be scaled up and supported in every HIV-care facility, as virological success could be also used to optimize treatment adherence and outcomes of APHIV.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment failure is common among HIV patients 7,8 . Poor adherence was strongly associated with virological failure among patients on ART 9,10 . HIV/AIDS patients should have an adherence level of at least 95% as a requirement for optimizing ART and maximizing virological suppression 11 …”
Section: Introductionmentioning
confidence: 99%